The association between serum vitamin C levels and respiratory infections in children and adolescents - Ci Li; Zhiwei Zhu; Shicai Jiang; Xiang Feng; Kaijie Gao; Tiewei Li; Liu Yang; Panpan Fang; Junmei Yang (Frontiers in Nutrition)
ObjectiveRespiratory infections (RIs) are a leading cause of morbidity and mortality, and vitamin C may play a vital role in the risk of RIs. However, high-quality evidence on the association between vitamin C and RIs in the younger population remains limited. This study aimed to investigate the association between serum vitamin C and RI risk in a nationally representative sample of children and adolescents.MethodsUtilizing data from the National Health and Nutrition Examination Survey (NHANES) 2017–2018, this study included 1,344 children and adolescents aged between 6 and 19 years old. Serum vitamin C levels were obtained from laboratory tests, and RIs were determined based on a self-reported health questionnaire. The association between vitamin C and RIs was tested using multivariable logistic regression models, interaction tests, and smoothing curve fitting.ResultsA total of 238 participants (17.7%) reported a respiratory infection in the past 30 days. Serum vitamin C was significantly and negatively associated with the risk of RIs in all regression models. After adjusting for all potential confounders, an increase of the vitamin C level by 10 units indicated a decrease of the RI risk by 7% (OR = 0.93, 95% confidence interval [CI]: 0.87, 0.99). Such an association remained consistently significant across subgroups with various demographical and health characteristics.ConclusionOur study shows a negative association between vitamin C and RIs among children and adolescents, highlighting the protective role of vitamin C against RIs. Our findings suggest that vitamin C supplementation may be potentially used for the prevention and treatment of RIs, which needs to be validated in future well-designed studies.